The Effectiveness of The Thematic Instructional Materials in Improving Social Sciences Basic Competence by Using Problem-Based Learning Model in Elementary School (Journal of Primary Education, 2019)
The objective of this study is to implement thematic instructional materials on Social Sciences Basic Competence through Problem Based Learning model in order to improve students learning achievement of V graders of elementary schools. This research method was an experiment method that was conducted in State Elementary Schools in Mejobo District, Kudus Regency through observation, interviews, questionnaires, and tests. The data were analyzed by using descriptive analysis, normality test, homogeneity test, independent t-test, and N gain value. The results of this research indicate that the implementation of thematic instructional materials Social Sciences Basic Competence has a significant effect on students’ learning achievement. This is indicated by the average score of the experiment class is higher than the control class. This effect is also strengthened by N gain score of students’ learning that is 0.47 in moderate category.